Demonstration of Platelet-Derived Microvesicles in Blood from Patients with Activated Coagulation and Fibrinolysis Using a Filtration Technique and Western Blotting - Andrè Holme, Pål; Olav Solum, Nils; Brosstad, Frank; Røger, Magnus; Abdelnoor, Michael (Thrombosis and Haemostasis, 1994)
Platelet vesiculation in vitro is correlated to platelet activation. It was therefore considered of interest to see if microvesicles (MV) are present in blood in clinical situations associated with platelet activation in vivo. Patients with both activated coagulation and fibrinolysis, implying that thrombin has been generated, suit such a purpose. Thus, the aim of this study was to investigate whether microvesicles could be detected in patients with activated coagulation and fibrinolysis, as diagnosed by the presence of soluble fibrin (positive ethanol gelation tests) and positive tests for fibrin degradation products (FDP). Platelet-rich plasma was prepared from citrated blood from patients (n = 22) and healthy controls (n = 32) matched as to age and sex. The intact platelets were removed from plasma by centrifugation. Any MV present were isolated from the platelet-free plasma by a filtration procedure, washed, solubilized in Triton X-100 and subjected to SDS-PAGE with Western blotting using a MAb against GPIIba as an indicator of the presence of microvesicles. All of the 22 patients showed the presence of microvesicles detectable by the content of GPIIba, whereas this could be observed in only 4 out of the 32 normal controls and then in small or trace amounts only. The presence of microvesicles among cell-derived material in the plasma of two of the patients was also confirmed by electron microscopy. To the best of our knowledge this is the first report on the presence of microvesicles in plasma from patients with both activated coagulation and fibrinolysis. Thus, the isolation of the microvesicles by the filtration technique allowed studies of the chemical composition of the microvesicles, and demonstrated the presence of microvesicles in situations where platelets are expected to have been activated in vivo and a tendency to thrombosis exists.